Development Strategy of Mutiara Farma Pharmacy, Babelan District, Bekasi Regency Through Telepharmacy Services - Saribu, Jimmi Ellyas Dolok; Liandhajani; Firdausi, Sri Rachmi (GoAcademica Research & Publishing, 2025)
The study explores the strategic development of Mutiara Farma Pharmacy in Babelan District, Bekasi, through the integration of telepharmacy services. Health issues, including those related to lifestyle, diet, and environmental factors, pose challenges to public health in Indonesia, highlighting the importance of accessible healthcare services. Telepharmacy has emerged as an innovative solution, enhancing drug accessibility, cost efficiency, and patient satisfaction, particularly in underserved areas. This research utilizes a qualitative descriptive approach, employing SWOT analysis, in-depth interviews, observations, and Focus Group Discussions (FGD) to assess the impact of telepharmacy on service quality, patient engagement, and financial performance. Findings indicate that telepharmacy offers significant advantages, such as improved healthcare accessibility, increased operational efficiency, and higher customer reach. However, challenges remain, including the absence of in-person interaction, data security concerns, and technological dependencies. Despite these challenges, telepharmacy's potential to overcome geographical barriers and provide remote healthcare services offers valuable benefits for Mutiara Farma Pharmacy. The study concludes that telepharmacy can enhance the sustainability of pharmacy services by improving patient care, though further research is needed to explore its broader impact on customer relationships and community reputation.